Fenomena FoMO pada Mahasiswa Berorganisasi di Yogyakarta - Rizqi Yuliana Mahadewi; Agasyita Kandhi Asmara; Rizma Kurniasari; Widya Juwita Sari (Universitas Sebelas Maret, 2025)
Students are required to be active not only in the classroom, but also outside the classroom and organization is one of the activities outside the classroom that students target to add experience and expand relationships. This is also one of the factors causing the FoMO phenomenon among students. This study aims to determine the picture of FoMO in students organizing at FIPP UNY. The research design used in this study was to use descriptive quantitative methods. This research was conducted on students organizing FIPP UNY batch 2021-2022. Samples were taken using random sampling using the Slovin formula so that 86 samples were obtained. Researchers collect data using questionnaires (self reports) distributed through google forms. Based on research that has been conducted from 86 respondents of students organizing at FIPP UNY, the results of the FoMO level in the medium category.